1992
DOI: 10.1038/bjc.1992.337
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of 3H-thymidine labelling index and flow cytometric S-phase in predicting survival of patients with non-Hodgkin's lymphoma

Abstract: Summary The 3H-thymidine labelling index (3H-dT LI) of cell suspensions from fresh material and the flow cytometric S-phase (FCM-S) of nuclei recovered from paraffin blocks were determined on the same pathologic lymph node specimen for 190 non-Hodgkin's lymphomas (NHLs). FCM-S was defined by a planimetric method and by an optimization procedure. Poor correlation coefficients were observed among the three cell kinetic variables. All

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In conclusion, Ki-67, MIB-1 or TLI cannot be considered as alternative proliferation indices, as already emerged in the only published comparative analysis of the clinical role of the former two markers (Rudas et al 1994). However, a possible complementarity of the different information provided by the proliferation markers, which already emerged for example for TLI and flow-cytometric S-phase cell fraction in non-Hodgkin's lymphomas (Costa et al 1992), needs to be investigated. Although the biological significance of the exposure of different or of an excess of antigens to microwave treatment of paraffinembedded material remains to be defined, the availability of MIB-1 should allow such comparative studies even on human solid tumours from archival material following formalin fixation, as well as prospective studies on routine material, once the fixation procedures are accurately standardized.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, Ki-67, MIB-1 or TLI cannot be considered as alternative proliferation indices, as already emerged in the only published comparative analysis of the clinical role of the former two markers (Rudas et al 1994). However, a possible complementarity of the different information provided by the proliferation markers, which already emerged for example for TLI and flow-cytometric S-phase cell fraction in non-Hodgkin's lymphomas (Costa et al 1992), needs to be investigated. Although the biological significance of the exposure of different or of an excess of antigens to microwave treatment of paraffinembedded material remains to be defined, the availability of MIB-1 should allow such comparative studies even on human solid tumours from archival material following formalin fixation, as well as prospective studies on routine material, once the fixation procedures are accurately standardized.…”
Section: Discussionmentioning
confidence: 99%
“…Previous DNA flow cytometric studies in NHL, though relatively scarce, mostly showed that the S-phase fraction (SPF), as an indicator of tumor proliferative activity, is associated with the histopathological grade of NHLs and the clinical outcome. [7][8][9][10][11][12][13][14][15] However, when mutually compared, the relative specific weight of SPF and grading as independent predictors of disease outcome is still controversial. 15 Likewise, the prognostic significance of DNA ploidy in NHL remains unclear.…”
mentioning
confidence: 99%
“…The prognostic role of S-phase cell fraction, determined by flow cytometry (FCM-S) or by autoradiography ([3H]dT LI), has been consistently evidenced in several studies on a series of patients including all histologies (Roos et al 1985, Lenner et al 1987, Griffin et al 1988, Silvestrini et al 1989b, Grierson et al 1990, Joensuu, Klemi & Jolkanen 1990, Rehn et al 1990, Costa et al 1992 (Table 3). The relevance of the S-phase cell fraction has also been maintained in multivariate analyses including morphology, symptoms, tumour stage and patient's age.…”
mentioning
confidence: 97%